Veränderung der Schulbuchaufgaben durch den Einsatz des grafikfähigen Taschenrechners im Analysisunterricht? (mathematica didactica, 2022)
This paper examines the influence of the use of graphic calculators on the tasks in calculus classes. In accordance with a mixed-method approach, a textbook analysis is carried out firstly using the method of qualitative content analysis. The data is subsequently evaluated quantitatively. The core of the analysis consists in the comparison of tasks from textbooks which were reissued for the use of graphic calculators and the respective previous editions. The focus is on the aspects 'calculation', `reasoning and interpretation', `data analysis', `visualization' as well as `result checking' known from previous studies and related to the graphic calculator. On this basis, it is possible to identify various in parts substantial changes which can be traced back to the intended use of graphic calculators.